Clinical implication of thiopurine methyltransferase polymorphism in children with acute lymphoblastic leukemia: A preliminary Egyptian study - El-Rashedy, Farida H.; Ragab, Seham Mohammed; Dawood, Ashraf A.; Temraz, Shaymaa A. (Indian Journal of Medical and Paediatric Oncology, 2015)
Background: 6-mercaptopurine (6-MP) is an essential component of pediatric acute lymphoblastic leukemia (ALL) maintenance therapy. Individual variability in this drug-related toxicity could be attributed in part to genetic polymorphism thiopurine methyltransferase (TPMT). Aim: To investigate the frequency of common TPMT polymorphisms in a cohort of Egyptian children with ALL and the possible relation between these polymorphisms and 6-MP with short-term complications. Materials and Methods: This study included 25 children. Data related to 6-MP toxicity during the maintenance phase were collected from the patients′ files. DNA was isolated and genotyping for TPMT G460A, and A719G mutations were performed by polymerase chain reaction-restriction fragment length polymorphism. Results: Twenty (80%) of the included 25 patients had a polymorphic TPMT allele. TPMTFNx013A was the most frequent (14/25, 56%), 8 patients were homozygous and 6 were heterozygous. TPMTFNx013C mutant allele was found in 4 patients (16%) in the heterozygous state while 2 patients (8%) were found to be heterozygous for TPMTFNx013B mutant allele. TPMT mutant patients, especially homozygous, were at greater risk of 6-MP hematological toxicity without significant difference regarding hepatic toxicity. Conclusions: TPMT polymorphism was common among the studied group and was associated with increased risk of drug toxicity. A population-based multi-center study is required to confirm our results.
Keywords: 6-mercaptopurine; acute lymphoblastic leukemia; pharmacogenetic; polymorphism; thiopurine methyltransferase